Production and comprehensive characterization of PVA/chitosan transdermal composite mats loaded with bioactive curcumin; evaluation of its release kinetics, antioxidant, antimicrobial, and biocompatibility features - Ciftci, Fatih; Ozarslan, Ali Can; Evcimen Duygulu, Niluefer (WILEY, 2024)
Recently, researchers have shown increasing interest in incorporating bioactive substances with therapeutic properties into fiber-structured mat biomaterials, which are favored as tissue scaffolds for wound healing applications. In this study, curcumin (Cur)-loaded polyvinyl alcohol (PVA)/chitosan (CS) composite mats were produced using the electrospinning method and followed by the freeze-drying method. Scanning electron microscope images proved the homogeneous structure of the composite mats, and Fourier transform infrared spectroscopy analysis showed that the Cur-loaded composite mats were successfully produced. The antibacterial activity of Cur-loaded PVA/CS composite mats was evaluated against Escherichia coli and Staphylococcus aureus, and the results showed that the antibacterial activity of the composite mats increased with the addition of Cur. Furthermore, the antioxidant test, release kinetics tests, and in vitro biocompatibility studies such as cytotoxicity, staining, and scratch assay of Cur-loaded PVA/CS composite mats were carried out. The results showed that adding Cur enhanced the bioactivity of PVA10/CS10 composite mats. Further, the biocompatibility findings indicated that 10Cur-PVA10/CS10 exhibited the highest viability value throughout all incubation periods compared with the other samples. Moreover, the highest rate of scratch closure on the 10Cur-PVA/10/CS10 composite mats was observed at the end of 24 h compared with the other composite mats. These findings indicate that the Cur-loaded PVA10/CS10 composite mats significantly positively impact cell migration and wound healing, making them a promising candidate as transdermal composite mats for tissue engineering and wound care applications.
Keywords: biodegradable; bioengineering; biomaterials; composites; fibers; ANTICANCER ACTIVITY; DRUG; NANOPARTICLES; NANOFIBERS; DELIVERY; Polymer Science